The influence of simulated global ocean acidification on the toxic effects of carbon nanoparticles on polychaetes - De Marchi, Lucia (2020)
Ocean acidification events are recognized as important drivers of change in biological systems. Particularly, the impacts of acidification are more severe in estuarine systems than in surface ocean due to their shallowness, low buffering capacity, low salinity and high organic matter from land drainage. Moreover, because they are transitional areas, estuaries can be seriously impacted by a vast number of anthropogenic activities and in the last decades, carbon nanomaterials (CNMs) are considered as emerging contaminants in these ecosystems. Considering all these evidences, chronic experiment was carried out, trying to understand the possible alteration on the chemical behaviour of two different CNMs (functionalized and pristine) in predicted climate change scenarios and consequently, how these alterations could modify the sensitivity of one the most common marine and estuarine organisms (the polychaeta Hediste diversicolor) assessing a set of biomarkers related to polychaetes oxidative status as well as the metabolic performance and neurotoxicity. Our results demonstrated that all enzymes worked together to counteract seawater acidification and CNMs, however oxidative stress in the exposed polychaetes to both CNMs, especially under ocean acidification conditions, was enhanced. In fact, although the antioxidant enzymes tried to cope as compensatory response of cellular defense systems against oxidative stress, the synergistic interactive effects of pH and functionalized CNMs indicated that acidified pH significantly increased the oxidative damage (in terms of lipid peroxidation) in the cotaminated organisms. Different responses were observed in organisms submitted to pristine CNMs under pH control, where the lipid peroxidation did not increase along with the increasing exposure concentrations. The present results further demonstrated neurotoxicity caused by both CNMs, especially noticeable at acidified conditions. The mechanism of enhanced toxicity could be attributed to slighter aggregation and more suspended NMs in acidified seawater (as demonstrated by the DLS analysis). Therefore, ocean acidification may cause a higher risk of CNMs to marine ecosystems.